A análise de discurso crítica - Magalhães, Izabel (Cadernos de Linguagem e Sociedade, 2010)
An issue for debate among CDA proponents is whether advocating critical assumptions exempts analysts from reflecting about their own practice. The issue is raised in relation to the discussion over the term adopted in Portuguese in the 1980’s by the University of Brasília Language and Ideology Research Group: ‘análise de discurso crítica (ADC)’.